2002
DOI: 10.1016/s0167-4889(02)00326-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines in liver failure and regeneration: potential new molecular therapies

Abstract: The liver is a unique organ, and first in line, the hepatocytes encounter the potential to proliferate during cell mass loss. This phenomenon is tightly controlled and resembles in some way the embryonal co-inhabitant cell lineage of the liver, the embryonic hematopoietic system. Interestingly, both the liver and hematopoietic cell proliferation and growth are controlled by various growth factors and cytokines. IL-6 and its signaling cascade inside the cells through STAT3 are both significantly important for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 124 publications
0
72
0
4
Order By: Relevance
“…The identification of endogenous protective mechanisms triggered upon liver injury is important not only for the study of the pathophysiology of this organ, but also for the design of more effective therapies that potentiate the natural defensive responses (13,24,56). The EGF-R is highly expressed in the hepatocyte and seems to be a relevant mediator of survival and proliferative responses (18 -20, 25-27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of endogenous protective mechanisms triggered upon liver injury is important not only for the study of the pathophysiology of this organ, but also for the design of more effective therapies that potentiate the natural defensive responses (13,24,56). The EGF-R is highly expressed in the hepatocyte and seems to be a relevant mediator of survival and proliferative responses (18 -20, 25-27).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of agents that reduce hepatocellular apoptosis is thus of special significance for the development of hepatoprotective therapeutics (12,13). Intensive research in this area has shown that cytokines such as interleukin-6 (IL-6), 1 growth factors like hepatocyte growth factor, or the hepatocyte-derived insulin-like growth factor binding protein-1 display potent hepatoprotective effects, including the attenuation of apoptosis induced by Fas ligation (14 -17).…”
mentioning
confidence: 99%
“…[1][2][3] It is unclear why some patients develop FH while others exposed to the same hepatic insult do not.…”
Section: F Ulminant Hepatitis (Fh) Is a Devastating Liver Dis-mentioning
confidence: 99%
“…F ulminant liver failure (FLF) 3 is a devastating liver disease that is associated with significant mortality (40 -80%) worldwide (1-3). The incidence of FLF has increased in the last decade accounting for Ͼ2000 deaths annually in the United States alone (2) and represents the reason for 11 and 30% of all liver transplants in Europe and the United States, respectively (1)(2)(3).…”
mentioning
confidence: 99%
“…The incidence of FLF has increased in the last decade accounting for Ͼ2000 deaths annually in the United States alone (2) and represents the reason for 11 and 30% of all liver transplants in Europe and the United States, respectively (1)(2)(3). FLF is a clinical syndrome that is characterized by the sudden onset of severe acute hepatitis with associated symptoms, including jaundice and hepatic encephalopathy in a patient with no previous history of liver disease (2,3). Viruses, drugs (such as acetaminophen), and toxins have all been identified as trigger factors of FLF (2, 3); however, in many patients (ϳ20%), the etiology of FLF remains unknown (1).…”
mentioning
confidence: 99%